Risk factors for mortality in pediatric tuberculous meningoencephalitis - Rahmayanti Rahmayanti; Nora Sovira; Anidar Anidar; Sulaiman Yusuf; Syafruddin Haris; Jufitriani Ismy (Indonesian Pediatric Society, 2026)
Background Tuberculous meningoencephalitis mortality rates remain high. The prognosis of tuberculous meningoencephalitis depends greatly on the timing of diagnosis, therapeutic response, clinical presentation, and resulting complications. Objective To identify the most significant risk factors associated with mortality in children diagnosed with tuberculous meningoencephalitis at Zainoel Abidin General Hospital, Banda Aceh. Methods This retrospective cohort study included pediatric patients diagnosed with tuberculous meningoencephalitis who were hospitalized at Zainoel Abidin General Hospital from January 2023 to December 2024. Data were collected from the medical records of 50 children who met the study criteria. Potential risk factors analyzed included decreased consciousness (GCS ≤12), hyponatremia, status epilepticus, hydrocephalus, and lack of BCG vaccination. Statistical analysis was performed using Chi-square and logistic regression tests. Results Of the 50 subjects, 60% were male, 46% were aged between 12 and 59 months, and 40% had good nutritional status. The overall mortality rate was 44%. Among the patients, 74% had a Glasgow coma scale (GCS) score ≤12, 52% presented with hyponatremia, 62% had status epilepticus, 66% developed hydrocephalus, and 72% had not received BCG vaccination. Bivariate analysis showed significant positive associations between mortality and GCS ≤12 (P=0.036), hydrocephalus (P=0.017), and lack of BCG vaccination (P=0.020). Multivariate analysis revealed that decreased consciousness (GCS ≤12) was the strongest predictor of mortality, with an odds ratio (OR) of 11.269 (95%CI 1.724–73.639; P=0.011). Conclusion Decreased consciousness, hydrocephalus, and lack of BCG vaccination are significantly associated with mortality in children with tuberculous meningoencephalitis. A GCS score of ≤12 is the most influential risk factor.